Comparación de nueve algoritmos de máquinas de aprendizaje con alicaciones en la detección de Arrecife de Coral. - Robertson, Neil M (2015)
This work focuses on the comparison of nine algorithms learning machines for the development of a detector coral this detector comprises a extraction portion eigenvectors , which is performed with filters Gabor Wavelets , and a sorting vector using learning machines based on neural networks comparing the accuracy and runtime nine machine learning algorithms , the result was realized that the algorithm selection decision trees.